Coupling of Active Learning Tools to Enhance Understanding of Fundamental Principles of Taylor’s Series and Generate Dynamic Class Room Environment with Healthy Social Interaction - Bhujakkanavar, Umesh; Jalwadi, Sudhindra; Patange, Sandip (Journal of Engineering Education Transformations, 2026)
Teaching in engineering education encompasses numerous curriculum factors and has become increasingly complex and challenging, particularly due to students’ short attention spans and difficulty in sustaining focus. This challenge is further intensified by the constant exposure to vast volumes of information in the digital era, making it harder to identify and retain meaningful learning content. This work proposes a systematic methodology that integrates and couples active learning tools through a coherent, symbiotic teaching–learning–evaluation process designed to foster a student-centred environment and nurture the joy of learning. The approach combines three complementary strategies—Think-Pair-Share (TPS), Concept Mapping, and Student Team Achievement Division (STAD)—and is implemented in a first-year engineering mathematics course. The lecture plan, learning activities, feedback mechanisms, and evaluation processes are developed at a micro-level to accommodate diverse learning styles and the psychological needs of contemporary learners. Quantitative and qualitative comparisons with the traditional teaching approach indicate notable improvements in self-confidence, critical thinking, innovation, and social interaction. Notably, end-semester examination scores increased by 28.49% compared to the traditional method, affirming the effectiveness of the integrated approach. Based on observations from a class of sixty students, statistical analysis performed using ANOVA software, results show that there is a positive improvement in the proposed methodology, but however reliability and consistency needs to be tested for heterogeneous range of students.